Speech and Language Abilities of Preschool Children Who Stutter - Petraki, Eirini; Lazaratou, Helen; Vlassopoulos, Maria (Advances in Social Sciences Research Journal, 2023)
Purpose: The purpose of this study was to examine speech and language differences between children who stutter without concomitant linguistic difficulties (CWS) and children who stutter with concomitant linguistic difficulties (CWS/CLD) on standardized tests of phonology, vocabulary and grammar. Method: Subjects were 20 children who stutter without concomitant linguistic difficulties (mean age= 5;1 years) and 21 children who stutter with concomitant linguistic difficulties (mean age= 4;9 years). All children were Greek-speaking. Each child participated initially in a 15-minute conversation with an adult. This conversational interaction was subsequently assessed to provide information pertinent to the child’s frequency and type of the speech dysfluency. Then, each child was administered standardized tests of phonology, vocabulary and grammar. Results: Results indicated that CWS and CWS/CLD did not differ in frequency and type of speech dysfluency. CWS did not show problems in developing phonology, vocabulary and grammar, while CWS/CLD lagged behind in phonology development although their vocabulary and grammar abilities were developing normally. Conclusion: Findings suggest that stuttering may appear in children with different speech and language profiles and for a subgroup of children, may be accompanied by a phonological disorder. Clinicians should take into account different aspects of speech and language when assessing and treating children who stutter and should have in mind the likelihood of comorbidity of stuttering with other developmental disorders in preschool children.